Visualizing disease the art and history of pathological illustrations - Bertoloni Meli, Domenico (The University of Chicago Press, 2018)
Visual anatomy books have been a staple of medical practice and study since the mid-16th century. But the visual representation of diseased states followed a very different pattern from anatomy, one we are only now beginning to investigate and understand. Domenico Bertoloni Meli explores key questions in this domain, opening a new field of inquiry based on the analysis of a rich body of arresting and intellectually challenging images reproduced here both in black and white and in colour.